(untitled) (Research, Society and Development, 2021)
Pyogenic granuloma is a very common non-neoplasic benign lesion in the oral cavity, being considered as a non-neoplasic proliferative process (NNPP). It is one of the entities most frequently associated with soft tissues expansions of the oral cavity, having preference for females, in the age group between the 2nd. and the 4th. decade of life. The treatment is by surgical excision with a small margin of safety, and irritants should be concomitantly removed for healing of the lesion. This study aimed to report a case of pyogenic granuloma in lower lip with casual trauma in a 20 - year - old male patient. The authors concluded by extolling the importance of the knowledge of oral pathology by the Dentist in order to perform a correct differential diagnosis of other lesions to perform the appropriate treatment.